2023
DOI: 10.1101/2023.10.24.563772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consistent higher emissions of carbon dioxide, nitrous oxide, and methane during the daytime in reservoirs

E. León-Palmero,
R. Morales-Baquero,
I. Reche

Abstract: Greenhouse gas (GHG) emissions from reservoirs are quantitatively relevant for atmospheric climatic forcing. These emissions have large temporal variability, with daily changes accounting for a substantial part of this variability. However, most estimations for GHG fluxes are based on the upscaling of discrete measurements performed during the daytime and, in general, they do not account for nighttime emissions. Here, we explored the daily patterns of CO2, N2O, and diffusive and ebullitive CH4fluxes in two eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…For instance, Liu et al 27 found that the seasonal pattern in N2O fluxes in Antarctic lakes was positively related to daily radiation, but they suggested that the increase of daily radiation may favor photosynthesis and thus stimulate N2O production from the decomposition of the algae. In our previous study, we consistently reported significant diurnal variation in the N2O emissions in two reservoirs in two different years, with N2O emissions up to one order of magnitude greater during the daytime than during the nighttime 17 . The experiments presented in this work indicate that solar radiation causes the production of N2O in abiotic conditions, and it may represent a significant source of N2O to the atmosphere which has not been reported previously o included in greenhouse gas budgets.…”
Section: Abiotic N2o Formation Driven By Sunlightmentioning
confidence: 60%
See 2 more Smart Citations
“…For instance, Liu et al 27 found that the seasonal pattern in N2O fluxes in Antarctic lakes was positively related to daily radiation, but they suggested that the increase of daily radiation may favor photosynthesis and thus stimulate N2O production from the decomposition of the algae. In our previous study, we consistently reported significant diurnal variation in the N2O emissions in two reservoirs in two different years, with N2O emissions up to one order of magnitude greater during the daytime than during the nighttime 17 . The experiments presented in this work indicate that solar radiation causes the production of N2O in abiotic conditions, and it may represent a significant source of N2O to the atmosphere which has not been reported previously o included in greenhouse gas budgets.…”
Section: Abiotic N2o Formation Driven By Sunlightmentioning
confidence: 60%
“…In a previous study we found recurrently higher N2O emissions during the daytime than during the nighttime during 24 hour flux measurement campaigns conducted in two different years in two reservoirs in southeast Spain with high inputs of N from catchments (i.e., Cubillas and Iznájar). Despite the differences in magnitude among years and reservoirs, this pattern in N2O emissions was consistent, and significantly correlated to the solar cycle 17 .…”
Section: Abiotic N2o Formation Driven By Sunlightmentioning
confidence: 81%
See 1 more Smart Citation